Biopestisida untuk Pengendalian Hama dan Penyakit Tanaman Aneka Kacang dan Umbi - Sumartini Sumartini (Puslitbang Tanaman Pangan, 2016)
Several types of pests and diseases in food crops must be controlled. Biopesticides use is one component of pest and disease control in an Integrated Pest Management (IPM). Biopesticides in Indonesia are still less popular, many people misinterpret biopesticides as organic farming, although many options of biopesticides are already available. Many botanical pesticides made from extract material herbs or spices are widely available and very popular, such as, galangal, neem and ginger. Since the effectiveness of biopesticides can not reach a hundred percent, it is advised to use them only for preventive purposes. Preparing biopesticides requires certain skills, therefore, farmers need to be supervised to be able to produce biopesticides by themselves. If many farmers already apply biopesticides in farming, the environment will less be polluted by toxic substances for humans. The paper reviews the effectiveness, application, constrains, benefits, and opportunities, as well as its development in Indonesia.